Geochemical heterogeneity of sand deposits and its implications for the provenance determination of Roman glass. Issue 2 (21st December 2015) - Brems, Dieter; Pauwels, Jente; Blomme, Annelore; Scott, Rebecca B.; Degryse, Patrick
Abstract: During the production of natron glass most features of the raw materials are lost and only some bulk geochemical characteristics have potential as provenance indicators. To determine the primary origin of archaeological glass artefacts, suitable sand raw materials have to be accurately characterised. In this respect, information about the possible variation in geochemical properties within a silica source is also vital to account for potential (partial) overlap of different sources. In this study, it is shown that the variation in major and minor elemental composition of beach sand on a local scale is smaller than the variation in Roman natron glass. Therefore, a single sand deposit can be seen as a relatively homogeneous source of silica for glass production. Nd isotopic signatures are identical for all samples analysed. The isotopic composition of Sr however varies considerably due to local variations in the relative proportions of carbonates and silicates (mostly feldspar).